Geometry Assurance Analysis Considering Riveting Distortion Effects Within The Aeronautical Domain - André Vinı́ cius Santos Silva; Luı́ s Gonzaga Trabasso; Marcio Fernandes Leroi (Journal of ICT, Design, Engineering and Technological Science, 2021)
Geometrical variations are intrinsic to all industrial manufacturing and assembly processes. Within the aeronautical domain, where there are many structural components on its products and small geometrical distortions have a great impact on the aircraft performance, the use of tools to estimate surface deviation plays a key role in defining well succeed manufacturing and assembly systems. Well-known methods to compute geometrical deviations nowadays consider statistical manufacturing process deviations and, in some cases, the flexibility of the assembly to estimate the final product surface distortion. The work presented herein describes a method that matches the deviations caused by the manufacturing process with deviations caused by the riveting process that is widely used in the aeronautical industry. The designed method was tested in an aeronautical commonly joint and showed that the riveting process plays an important role in amplifying surface errors. The finding underlines the importance of considering the riveting process effects on analyzing the geometrical variations for aeronautical product surfaces.